Inhibition effect of apium graveolens, punica granatum, and camellia sinensis extracts on plain carbon steel. Issue 1 (1st January 2020) - Loto, Roland Tolulope; Loto, Cleophas Akintoye
Abstract: Application of plant extracts for corrosion inhibition of carbon steels continues to increase due to their nontoxic nature and presence of phytochemical components. The corrosion inhibition performance of Apium graveolens, Punica granatum, and Camellia sinensis plant extracts on plain carbon steel in 0.5 M sulfuric acid was assessed with coupon measurement, potentiodynamic polarization technique and optical microscopy characterization. The plant extracts effectively inhibited the carbon steel from 60% to 90% concentration with optimal inhibition efficiency values of 95.83%, 87.08%, and 92.37% at 90% concentration from coupon measurement. The corrosion inhibition capability of the plant extracts proves it to be time and concentration dependent, though time dependence decreases with increase in concentration and was negligible at 90% concentration. Polarization studies showed the extracts exhibited cathodic inhibition mechanism from the displacement of the polarization plots and significant decrease in cathodic portion of the polarization plots. Optical image of the steel without the extracts exhibited general corrosion with macro-pits which significantly differ from the image of the inhibited steel.